An interactive procedure of a transverse beam matching and correction in INR Linac - Bragin, S.E.; Feschenko, A.V.; Grekhov, O.V.; Lebedeva, N.F.; Mikhailov, V.N.; Mirzojan, A.N.; Moiseev, V.A.; Volodkevich, O.M. (Вопросы атомной науки и техники, 2006)
An application package is developed to carry out an interactive procedure for a transverse beam matching and correction in INR Linac. The results of multiple beam profile measurements in several accelerator areas are used. The currents in steering coils are found to suppress the beam displacement. The gradients in quadrupole lenses are calculated to match the beam. This procedure is successfully used in accelerator tuning.